2013
DOI: 10.1063/1.4806999
|View full text |Cite
|
Sign up to set email alerts
|

Direct monitoring of minority carrier density during light induced degradation in Czochralski silicon by photoluminescence imaging

Abstract: In this paper, we present a new method for studying the light induced degradation process, in which the minority carrier density is monitored directly during light soaking by photoluminescence imaging. We show experimentally that above a certain minority carrier concentration limit, Δnlim, the boron oxygen (B-O) defect generation rate is fully independent of the injected carrier concentration. By simulation, we determine Δnlim for a range of p-type Czochralski silicon samples with different boron concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…This cannot be the rate determining step [4], but it also means that none of the earlier steps can be rate determining since the reaction does not start until the excess carriers are present.…”
Section: Rate Determining Stepmentioning
confidence: 99%
See 3 more Smart Citations
“…This cannot be the rate determining step [4], but it also means that none of the earlier steps can be rate determining since the reaction does not start until the excess carriers are present.…”
Section: Rate Determining Stepmentioning
confidence: 99%
“…Step 1 (6) can under any circumstances not be rate-determining since the rate of the defect reaction is independent of Δn [4].…”
Section: Rate Determining Stepmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Naerland et al 28 have also shown that increasing the illumination intensity increases the degraded area due to excess carrier diffusion. Figure 1 presents the high-injection level lifetime as a function of illumination time at intensities 1 and 18 W/cm 2 in an oxidized top mc-Si sample with positive corona charge (þ4 lC/cm 2 ), while Figure 2 shows the corresponding medium injection lifetime maps before and after illumination.…”
Section: A Lid As Function Of Bias Light Intensitymentioning
confidence: 99%